Proposição de um modelo de custeio para a indústria da construção civil - subsetor edificações: adaptação do custo-meta - Muniz, Alyne Valentim (2006)
The civil architecture sector has a considerable importance to the country’s economy, totaling 15% of the GDP, and generating 15 million jobs. The building making subsector is responsible for the reduction of the housing deficit. Nevertheless, a major characteristic of such subsector is the fragmentation of the market in other words, several companies compete in the same segment. Thus, the companies need managerial systems aiming to lower costs and enhance their competitive strategies. In the building making subsector, most costs are incurred in product development, leading to the identification of a method in the Theory of Target Cost, which would suit the subsector, as it is a competition oriented system with the purpose of reducing product development cost. As a consequence, the purpose of this study is to propose a cost model for product development of the civil architecture sector, in the building making subsector, adapted from the target cost. In this sense, theoretical approaches about the civil architecture sector strategic management, and the target cost were considered. Moreover, the methodology used in this study coincided with a fieldwork and a case study. The fieldwork included taking survey of companies registered in the Civil Architecture Sector Union of the State of Ceará aiming to describe the profile and management methods of the companies integrating the sector and contribute to the formulating of a cost model. The main purpose of this study was the proposal of a cost model to the civil architecture sector, in the building making subsector. Its application can be verified through a case study in a company of the subsector, where the contributions of the model are perceived in terms of clear cost effectiveness, competitive sales price, and profit margin.